MusTIC: Research and Innovation Group on Music, Technology, Interactivity and Creativity - Calegario, Filipe; Cabral, Giordano; Ramalho, Geber (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
MusTIC is a research and innovation group concerned in conceiving and developing products and experiences that have an impact on music, education, visual and performing arts, and entertainment. In particular, we have been working with tools, methods, and concepts from physical computing, interaction design, and signal processing to build new interfaces for artistic expression, to develop tools for rapid prototyping, and to improve education through robotics and gamification.